Group coaching interventions and its effects on learner autonomy / Siew Foen Ng, Moniza Abdullah and Gary J. Confessore - Foen Ng, Siew; Abdullah, Moniza; Confessore, Gary J. (Universiti Teknologi MARA Shah Alam, 2017)
In the Malaysian context, after 11 years of formal education, many students still find themselves trapped in situations in which they are unable to exercise autonomous learning skills such as taking initiative in projects, being resourceful in difficult situations, persistent in pursuing goals and flexible in selecting appropriate learning approaches. This phenomenon occurs because of the fact that Malaysian learners have been exposed ingrained with rote learning processes through the primary and secondary school systems. This study assessed the effect on Learner Autonomy Profile V3.0 (LAP) scores of a five-week coaching intervention for pre-diploma students at one university in Malaysia. Seven faculty members of University Teknologi Mara (UiTM) Kelantan were trained to serve as Certified Learner Autonomy Coaches (CLACs) and held coaching intervention sessions weekly for seven to nine students assigned to each of them for five weeks. Coaching in this higher education environment utilized scores from an instrument that was designed to elicit the extent to which respondents claim to possess behavioral intentions associated with learning. Coaches used these responses to guide the individual students through a series of steps to recognize those behavioral intentions that are most likely to undermine and those that enhance their learning efforts. The findings indicate that the student group that had undergone the coaching sessions benefited academically and the coaching interventions had a positive impact on students' behavioral intentions to learn.